2012
DOI: 10.1121/1.3699207
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of cochlear distortion products as slow waves: A comparison of experimental and model data

Abstract: There is a long-lasting question of how distortion products (DPs) arising from nonlinear amplification processes in the cochlea are transmitted from their generation sites to the stapes. Two hypotheses have been proposed: (1) the slow-wave hypothesis whereby transmission is via the transverse pressure difference across the cochlear partition and (2) the fast-wave hypothesis proposing transmission via longitudinal compression waves. Ren with co-workers have addressed this topic experimentally by measuring the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…The present study supplies new experimental evidence that supports Vetesnik and Gummer's (2012) conclusion. At narrow f 2 /f 1 ratios, where much of the data supporting IDWP were obtained, the present findings revealed complexities in the DPOAE time waveforms.…”
Section: Relevance To Idwpsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study supplies new experimental evidence that supports Vetesnik and Gummer's (2012) conclusion. At narrow f 2 /f 1 ratios, where much of the data supporting IDWP were obtained, the present findings revealed complexities in the DPOAE time waveforms.…”
Section: Relevance To Idwpsupporting
confidence: 77%
“…To obtain a more detailed insight into this problem, Vetesnik and Gummer (2012) compared the data of Ren and colleagues (Ren, 2004;He et al, 2008He et al, , 2010 to simulations of their experiments in a nonlinear cochlear model of DPOAE generation. From this analysis, they concluded that the appearance of the IDWP for DPOAEs might have been due to the DPOAE being at least partially generated basal to the measurement site.…”
Section: Relevance To Idwpmentioning
confidence: 99%
“…The result is a measurable interference pattern near CF. As discussed elsewhere (Sisto et al, 2011;de Boer et al, 2011;Vetesnik and Gummer, 2012), analogous reasoning explains why studies that have used distortion products to look for reversetraveling waves on the BM have had difficulty finding them (e.g., Ren, 2004;He et al, 2008;de Boer et al, 2008)-the reverse wave, although present, is swamped out by the forward wave that subsequently arises from reflection at the stapes and is then boosted by the cochlear amplifier.…”
Section: A Bm Ripples and Standing Wavesmentioning
confidence: 99%
“…Another recent theoretical approach (254) examines several conventional models of sound propagation in the cochlea, which consistently predict that slow reversetraveling transverse waves can produce negative phase slopes if two conditions are met: a broad enough distribution of DP sites of generation and a reasonably large stapes reflectivity. Even more recently, application of a two-dimensional nonlinear hydrodynamic cochlea model (283) to the analysis of Ren's experiments suggested that the DP generation sites were well basal to the measurement sites, thus reconciling the negative phase slopes with the possibility of slow-wave backward propagation. The distribution of generation sites basal to the f 2 CF location was estimated to 0.5 mm for f 2 ϭ 12 kHz, which emphasizes, once again, two important caveats.…”
Section: H Dpoaes: Their Timing and Backward Propagationmentioning
confidence: 97%